2017
DOI: 10.13189/ujer.2017.050603
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Static and Dynamic Balance and Anticipation Time, Reaction Time in School Children at the Age of 10-12 Years

Abstract: The aim of this study is to investigate the relationship between anticipation time, reaction time and balance characteristics in school children at the age of 10-12 years.11 males and 12 females, 23 students in total, studying at Istanbul Sancaktepe Ibn-i Sina Elementary School, whose average age was 11.06 years, average height was 142.78 cm and average weight was 37.6 kg, voluntarily participated in the study. Height, body weight, anticipation time, reaction time, static balance and dynamic balance measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
7
1
1
Order By: Relevance
“…Bozkurt, Erkut & Akkoç (2017) found a significant relationship between anticipation time and reaction time in the study conducted with school students at the average age of 11.06 years (p<0.05). These perceptual motor skills affect each other as seen above.…”
Section: Discussionmentioning
confidence: 80%
“…Bozkurt, Erkut & Akkoç (2017) found a significant relationship between anticipation time and reaction time in the study conducted with school students at the average age of 11.06 years (p<0.05). These perceptual motor skills affect each other as seen above.…”
Section: Discussionmentioning
confidence: 80%
“…This finding supports the notion of stable magnitude of interlateral asymmetries of performance during motor development. Bozkurt et al [22] found a positive relationship was found between the hard floor and the right foot and left foot dynamic balance measurements (p<0.05), Teixeira et. al.…”
Section: Discussionmentioning
confidence: 90%
“…Previous investigations, especially regarding RT, failed to present an ecological task to assess RT [ 15 , 32 , 51 , 60 ]. For instance, most previous investigations used simple software computer tasks and not a real-life scenario (i.e., lower ecological validity) such as the one utilized in the present study.…”
Section: Discussionmentioning
confidence: 99%